Gout in the UK and Germany: prevalence, comorbidities and management in general practice 2000–2005. Issue 7 (2nd November 2007) - Annemans, L; Spaepen, E; Gaskin, M; Bonnemaire, M; Malier, V; Gilbert, T; Nuki, G
Abstract : Objective: To investigate and compare the prevalence, comorbidities and management of gout in practice in the UK and Germany. Methods: A retrospective analysis of patients with gout, identified through the records of 2.5 million patients in UK general practices and 2.4 million patients attending GPs or internists in Germany, using the IMS Disease Analyzer. Results: The prevalence of gout was 1.4% in the UK and Germany. Obesity was the most common comorbidity in the UK (27.7%), but in Germany the most common comorbidity was diabetes (25.9%). The prevalence of comorbidities tended to increase with serum uric acid (sUA) levels. There was a positive correlation between sUA level and the frequency of gout flares. Compared with those in whom sUA was <360 μmol/l (<6 mg/dl), odds ratios for a gout flare were 1.33 and 1.37 at sUA 360–420 μmol/l (6–7 mg/dl), and 2.15 and 2.48 at sUA >530 μmol/l ( >9 mg/dl) in the UK and Germany, respectively (p<0.01). Conclusions: The prevalence of gout in practice in the UK and Germany in the years 2000–5 was 1.4%, consistent with previous UK data for 1990–9. Chronic comorbidities were common among patients with gout and included conditions associated with an increased risk for cardiovascular disease, such as obesity, diabetes and hypertension. The importance of regular monitoring of sUA in order to tailor gout treatment was highlighted by data from this study showing that patients with sUA levels ⩾360 μmol/l (⩾6 mg/dl) had an increased risk of gout flares.